A passive islanding detection method for hybrid distributed generation system under balanced islanding - Ramireddy chilakala; K Suresh; P Anusha; Sk Najma; B. I. Rajkumar; B. Prasanna Lakshmi (Institute of Advanced Engineering and Science, 2019)
To solve the energy consumption demand of the world and environmental problems in the future the distributed generation is considered an alternative approach. In this paper a new passive islanding detection technique was proposed for the Hybrid distributed generation (HDG) system based on changes in negative sequence voltage (NSV) and currents during an unintentional islanding. Islanding is caused in the distributed generation system due to failures in the power grid. As per distribution energy resources interconnection standards, it should be detected within 2 sec with the equipments connected to it. It is difficult to detect islanding during zero power imbalance condition. Sequence analyzer will separate the positive, negative and zero sequence components of voltages and currents from the voltages and currents obtained at the point of common coupling (PCC). During a wide range of power imbalance conditions the change in negative sequence voltage and currents are examined for islanding detection. The simulation shows that this method is free from Non detection zone, even at zero power imbalances between load and distribution generation. The computer simulations made in Matlab/ Simulink laboratory show the effectiveness of this method